2008
DOI: 10.1111/j.1572-0241.2008.01920.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Ionizing Radiation Exposure in a Population-Based Cohort of Patients with Inflammatory Bowel Disease

Abstract: Objective-For diagnosis, assessing disease activity, complications and extraintestinal manifestations, and monitoring response to therapy, patients with inflammatory bowel disease undergo many radiological studies employing ionizing radiation. However, the extent of radiation exposure in these patients is unknown.Methods-A population-based inception cohort of 215 patients with inflammatory bowel disease from Olmsted County, Minnesota, diagnosed between 1990 and 2001, was identified. The total effective dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(69 citation statements)
references
References 53 publications
0
67
1
1
Order By: Relevance
“…Also concerning is our finding of the independent effect of psychiatric co-morbidity on undergoing abdominal imaging studies, primarily CT scans. We were not able to ascertain whether the imaging studies obtained were appropriate, but several recent studies have highlighted the high frequency of radiographic studies in CD patients [41][42][43] . Thus, it is important for treating physicians to recognize underlying psychiatric co-morbidity could be a potential risk factor for multiple radiologic studies, to practice judicious use of imaging studies and use alternate imaging modalities such as magnetic resonance imaging (MRI) studies wherever indicated and possible in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Also concerning is our finding of the independent effect of psychiatric co-morbidity on undergoing abdominal imaging studies, primarily CT scans. We were not able to ascertain whether the imaging studies obtained were appropriate, but several recent studies have highlighted the high frequency of radiographic studies in CD patients [41][42][43] . Thus, it is important for treating physicians to recognize underlying psychiatric co-morbidity could be a potential risk factor for multiple radiologic studies, to practice judicious use of imaging studies and use alternate imaging modalities such as magnetic resonance imaging (MRI) studies wherever indicated and possible in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the concept of "effective dose" was introduced. This term, measured in millisieverts (mSv), reflects an attempt to create a standard metric that quantifies the impact of the absorbed radiation (Peloquin et al, 2008). Effective dose is calculated by multiplying the absorbed radiation dose by a conversion factor for the body segment that was imaged; this conversion factor varies based upon the radiosensitivity of the exposed organs.…”
Section: Special Considerations In the Pediatric Populationmentioning
confidence: 99%
“…Multiple retrospective studies have reported radiation exposures in CD patients to be higher than that of the general population [7,8]. The use of CT in patients with inflammatory bowel disease (IBD) has increased noticeably in the last decade with an 840 % increase from 2003 to 2007 reported at one institution [9]. A retrospective cohort study of 415 patients over 20 years found that usage of CTs increased by 310 % and that 1 in 13 patients was exposed to potentially harmful levels of ionizing radiation defined as CED [50 mSv.…”
mentioning
confidence: 99%